A STUDY ON INDUSTRIAL RELATION IN SIRUVANI CLOTHING, COIMBATORE - Dr. M. Alaguthankamani , Dr. A. Kavitha (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The title of the project is “INDUSTRIAL RELATION IN SIRUVANI CLOTHING PRIVATE LIMITED, COIMBATORE”. The core objective of the research is to make out the industrial relation. The research design used in this study is descriptive research design. A sample size of 105 employees was randomly selected from Siruvani clothing private limited. Data was collected by survey method through prepared questionnaire. The primary data was collected through questionnaire and secondary data from websites, journals, magazines, and library.The term Industrial Relations” comprises industry and relation”.‘Industry and Relations ‘Industry means ‘any productive activity in which an individual is engaged’, and Relations means ‘The relations that survive in the industry between the employer and his workmen’.“Industrial relation is an art, the art of living together for purposes of production”-The study was done through simple percentage and chi-square test. From the analysis it found that their contented with working place and safety measures provided by the organization.